Determinación de arsénico en sedimento marino por espectrocopía atómica mediante su hidruro volátil generado electroquímicamente - Alvarado, José (2015)
In this study, the determination of arsenic in marine sediment of Bajo Alto Commune, Province of El Oro, Ecuador is described. The electrochemical generation of this volatile metallic hydride (arsine), was carried out using an amalgam cathode Au Hg gold mercury in a 0.5M H2SO4 solution. The results were compared with those obtained with other commonly used cathodes for generating this metal hydride. The results show that the marine sediments are not contaminated by arsenic. The concentration of mercury was 0.05 mg of kg, while the permitted limit according to the World Health Organization is 5mg of Kg. In addition, the cathode of Au, Hg has better tolerance to interference and repeatability of the cathodes of Au, Pt, Pb or reticulated glass carbon (RGC). The accuracy of the method was verified by determining As in a certified reference material.